Active to Reactive Power Attack in Interconnected Electric Power Systems and Electric Vehicle Charging Stations - Beheshteh Raouf; Seyedamirabbas Mousavian (IEEE Access)
Vehicle-to-grid is a promising technology that can improve the power system’s stability and controllability. Despite these advantages, it could also create new threats to the power system’s security. A novel switching attack initiated from electric vehicle charging stations against the power system was investigated. In this attack, a portion of electric vehicles at each bus were compromised to switch from charging active power to discharging reactive power during peak hours. The results demonstrate that the switching attack disrupts the power system and causes significant over-voltages. The highest levels of over-voltage were observed when the attacker identified the most vulnerable buses and altered the charging and discharging pattern of electric vehicles. It was shown that a Jacobian-based method can be used to identify the most sensitive buses.